1984
DOI: 10.1007/bf00687342
|View full text |Cite
|
Sign up to set email alerts
|

Neuropathologic study on chronic neurotoxicity of 5-fluorouracil and its masked compounds in dogs

Abstract: 5-Fluorouracil (FU) and its masked compounds tegafur (FT) and carmofur (HCFU) were administered orally to Beagle dogs daily for 6 months, and their chronic neurotoxic effects were examined morphologically. In ten dogs that survived the 6-month treatment large vacuoles produced by splitting of the intraperiod line of myelin were observed in the fornix in the wall of the third ventricle. In severely affected dogs large vacuoles developed in the medial preoptic area, medial portion of the internal capsule, the ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

1985
1985
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 23 publications
1
22
0
Order By: Relevance
“…The present results therefore support the earlier report of Davis et al (1994). These authors demonstrated that GW776 protected dogs from the neurotoxicity induced by a 26-h continuous infusion of 5-FU at three doses (1.6, 4 or 16 mg kg-' 24 h-') and suggested with others (Koenig and Patel, 1970;Okeda et al, 1984Okeda et al, , 1990) that 5-FU catabolites are responsible for this dose-limiting toxicity in dogs and cats, which are particularly sensitive.…”
Section: Proportions Of 5-fu and Its Metabolitessupporting
confidence: 93%
See 1 more Smart Citation
“…The present results therefore support the earlier report of Davis et al (1994). These authors demonstrated that GW776 protected dogs from the neurotoxicity induced by a 26-h continuous infusion of 5-FU at three doses (1.6, 4 or 16 mg kg-' 24 h-') and suggested with others (Koenig and Patel, 1970;Okeda et al, 1984Okeda et al, , 1990) that 5-FU catabolites are responsible for this dose-limiting toxicity in dogs and cats, which are particularly sensitive.…”
Section: Proportions Of 5-fu and Its Metabolitessupporting
confidence: 93%
“…GW776 greatly improved the anti-tumour efficacy, the oral bioavailability and the therapeutic index of 5-FU in animals (Baccanari et al, 1993;Cao et al, 1994). Moreover, Davis et al (1994) demonstrated that GW776 protected dogs from 5-FU-induced neurotoxicity that could be due to FAC (Koenig and Patel, 1970;Okeda et al, 1984Okeda et al, , 1990.…”
mentioning
confidence: 99%
“…Vacuolization of myelinated central nervous system tissues have been reported with its use (16). Topical 5-FU has been found to cause conjunctivitis, blepharitis, circumorbital edema, ocular pain, and corneal ulceration (11,22).…”
Section: Commentmentioning
confidence: 99%
“…Okeda et al [8,9] investigated carmofur-induced encephalopathy neuropathologically in dogs and cats, and found intramyelinic edema, including vacuole formation. Vacuoles measured 20±50 mm in diameter and were produced by splitting of the intraperiod line of myelin and necrosis without myelin destruction.…”
Section: Discussionmentioning
confidence: 98%